Analisis Yuridis Kontrak Sewa Menyewa atau Jual Beli Akun Bisnis E-Commerce di Indonesia - Pratama, Dito Alif; Nasution, Rachmad Saleh (Prodi Ekonomi Syariah, Fakultas Syariah, Institut PTIQ Jakarta, 2024)
This research examines the legal and economic impacts of the practice of renting e-commerce business accounts from a legal and sharia perspective. The analysis shows that the current legal regulations have not fully accommodated the complexity of this practice. Although the ITE Law and regulations related to electronic transactions provide a basic framework, the lack of specifications regarding account renting causes legal uncertainty for both renters and account owners. Renters face the risk of breach of contract and legal issues related to the use of other parties' identities, while account owners may lose control over their account activities and face legal consequences from the renter's actions. Many business actors ignore or do not fully comply with regulations due to the lack of effective and clear law enforcement. From an economic perspective, renting e-commerce business accounts offers significant benefits to both parties. Renters can access a wider market and increase the credibility of their business, while account owners earn passive income from rental fees. However, the risk of financial loss remains if the rented account experiences problems or is blocked by the e-commerce platform. Account owners also risk losing income if their accounts are blocked due to violations by renters. The views of Islamic economic scholars emphasize honesty and fairness in transactions, avoiding uncertainty (gharar). The Hadith prohibits buying and selling that contains gharar (HR. Muslim). Regulations such as the ITE Law and the Consumer Protection Law also prohibit illegal access and misleading transactions. This study highlights the importance of more specific regulations and stronger legal protection. Compliance with regulations needs to be improved, and clear contracts and financial protection mechanisms must be established to manage risks. Thus, the practice of renting e-commerce business accounts can run more safely and efficiently, providing optimal economic benefits for all parties involved.